Does commercial orientation matter for policy-game framing? A content analysis of television and radio news programmes on public and private stations. (August 2014) - Rafter, Kevin; Flynn, Roddy; McMenamin, Iain; O'Malley, Eoin
This article examines the relationship between different ownership types in broadcast news to determine the portrayal of election coverage as a strategic game against a focus on policy issues. Using a content analysis of six television and radio programmes during the 2011 Irish general election, we test hypotheses about differences in coverage provided by public service programming with equivalent private sector coverage. Our findings improve upon two key aspects of earlier research on game-policy frames. First, we show that commercial outlets can produce content that has democratic value, and suggest that before reaching definitive judgements not only it is necessary to distinguish between radio and television programmes but it is also advisable to study individual programming on each medium. Second, in a key market segment, we show that there is a clear distinction between editorial choices on policy content between public and private radio. These findings suggest that policy-orientated private programming may react to factors such as a culture of public service broadcasting as well as regulatory interventionism. We also suggest that there are cases where policy-rich private programming is driven by different editorial values from its public counterpart which can benefit the public.